Womenomics and Migrant Workers Policy: Can They Solve Labor Shortage in Japan? - Emmanuel Pradipta; Bevaola Kusumasari (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
Aging population threatens economic conditions in Japan which results in a condition of labor shortage, furthermore the government provides Womenomics’ and accepting migrant workers policy to solve the issue. This research aims to give an understanding about Japan’s labor shortage condition and how it can be solved by Womenomics and accepting migrant workers. Therefore, this research emphasized the labor shortage conditions and the failure factors of Womenomics’ and accepting migrant workers in Japan. Essentially, this study applied the qualitative case study method by referring to the literature review conducted by previous studies. The findings of this research are meant providing suggestions to Japan’s government about how important it is to enforce appropriate policies to tackle labor shortages and to minimize policy failure of policy implementation.